2019
DOI: 10.1021/acs.langmuir.9b02732
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing the Oil-like and Surfactant-like Behavior of Polar Oils

Abstract: In this work, a bifunctional model was developed to fit and predict the phase inversion point (PIP) of microemulsions containing polar oils. This model incorporated the hydrophilic−lipophilic difference (HLD) equations, where HLD = 0 at the PIP. The model uses a Langmuir isotherm to account for the interfacial segregation of polar oils as a function of their concentration in the bulk oil phase. The segregated polar oil was treated as being surfactant-like, having a characteristic curvature (Cc). The polar oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 59 publications
1
58
0
Order By: Relevance
“…For partitioning polar oils, added at relatively low concentrations (often less than 20 mol%) in relation to the surfactant, previous work has found that values of q max ~0.7 are appropriate for the segregation-bifunctional model (Ghayour & Acosta, 2019). However, in our preliminary simulations, we determined that if the ratio C j /C np was larger than 0.7, then using q max = 0.7 produced an overestimation of the partition of these species.…”
Section: Model Developmentmentioning
confidence: 66%
See 3 more Smart Citations
“…For partitioning polar oils, added at relatively low concentrations (often less than 20 mol%) in relation to the surfactant, previous work has found that values of q max ~0.7 are appropriate for the segregation-bifunctional model (Ghayour & Acosta, 2019). However, in our preliminary simulations, we determined that if the ratio C j /C np was larger than 0.7, then using q max = 0.7 produced an overestimation of the partition of these species.…”
Section: Model Developmentmentioning
confidence: 66%
“…To represent the polar oil segregation of the partitioning surfactant species in the surfactant pseudophase using a Langmuir isotherm, one needs two parameters, q max,j and Km j , such that q j = q max,j ÁKm j ÁCe j /(1 + Km j ÁCe j ). This segregation approach was previously validated for naphthenic acid and dodecanol, used as an example of polar oils, with ionic and nonionic surfactants (Ghayour & Acosta, 2019, 2020. The segregation-bifunctional model has also been used to predict the phase behavior of cosmetic formulations for skin cleaning, including cholesterol and oleic acid as polar oils (Acosta, 2020); and to evaluate the effect of polar oils (oleic acid) in oily substrates removed with a detergent formulation based on alkyl ethoxylates (Natali & Acosta, 2019).…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…F(S) is the function of salinity, being expressed as Ln(S) and b(S) for ionic and nonionic surfactants, respectively. Equivalent Alkane Carbon Number ( EACN ) represents oil hydrophobicity 10 and f(A) is the function of alcohol, which usually acts as co-surfactant or co-solvent in the system 11 . It is expressed as m a C a in the HLD formulation, where m a is a constant value depending on the alcohol type and C a represents its concentration 12 .…”
Section: Introductionmentioning
confidence: 99%